Sleep quality mediates the association between tea consumption and duration of COVID-19-related symptoms in middle-aged and elderly adults (aged 50 and above) - Fan, Yuxin; Zhu, Yaonan; Wang, Yunyu; Jiang, Jun; Yang, Shaopeng; Lu, Jie; Ma, Qinghua; Zhu, Hong (Frontiers in Psychiatry, 2025)
ObjectivesThe association between tea consumption and the duration of COVID-19-related symptoms remains inconclusive. This cross-sectional study investigates the potential mediating role of sleep quality in this association. The association between tea consumption and the duration of COVID-19-related symptoms remains inconclusive. This cross-sectional study aims to investigate the potential mediating role of sleep quality in this association.MethodsWe conducted a cross-sectional study using data from middle-aged and elderly adults (aged 50 and above) in Weitang Town in 2023. Detailed information on tea consumption, duration of COVID-19-related symptoms, and sleep quality was collected through face-to-face interviews using pre-designed questionnaires. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), which evaluated sleep quality over the past month during the acute phase of COVID-19. Spearman correlation analysis was employed to examine the relationships between variables. mediation analysis utilized a mediation model with multi-category independent variables.ResultsTea consumption was negatively associated with sleep quality, which in turn was positively associated with COVID-19 symptom duration. Mediation analysis showed sleep quality partially mediated the relationship between daily tea drinking and symptom duration, and fully mediated associations between green tea consumption, tea drinking for <15 or ≥30 years, tea concentration, and symptom duration. The mediation effect accounted for 11%–21% of the total effect.ConclusionsTea consumption is associated with shorter duration of COVID-19-related symptoms, with sleep quality acting as a mediator. These findings highlight the potential of improving sleep quality to reduce symptom duration, but conclusions are limited by the cross-sectional design.